P-106 Regional collaboration facilitates delivery of palliative care research in the west midlands. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Ferguson, Claire
Abstract : Background: Within the West Midlands there are a number of palliative care services which are actively engaged in research whilst others are working to become 'research ready'. Aims: To increase research activity within palliative care providers across the West Midlands; To develop and conduct original research in these settings across the West Midlands; To support delivery of the National Institute for Health Research (NIHR) and Charities Consortium for Hospice and Community Research objectives. Methods: A collaborative network was formalised in 2018, which meets quarterly and is made up of clinical and non-clinical staff that represent: Hospices; NHS community palliative care services; NIHR senior research staff for supportive and palliative care; University representatives; A representative from the registrar–led West Midlands research collaborative. Results: Meetings are attended by over 10 organisations and this number continues to increase. Feedback on being part of the group includes: Excellent networking opportunities and a useful forum for problem solving; Helpful with job descriptions and interview questions for recruiting research nurses; Useful for gaining ideas of how to promote research within a hospice and to hospice Boards; Has enabled us to identify studies to which we could recruit patients and become part of the study; Being able to discuss a research project with other organisations before deciding whether it was appropriate to put in an expression of interest; NIHR research nurses have reported improved ability to signpost potential studies and training opportunities through the group. Conclusions: So far, the group has led to an increase in recruitment to portfolio studies within the region and is helping to establish the infrastructure that will enable through collaborative working the development of original research projects.